A Number Theoretic Approach to Sylow r-Subgroups of Classical Groups - I. Alali, Mashhour; Hering, Christoph; Neumann, Anni (Revista Matemática Complutense, 2005)
The purpose of this paper is to give a general and a simple approach to describe the Sylow r-subgroups of classical groups.